Pengelolaan lingkungan internasional. Dari sudut pandang negara sedang berkembang - [Tidak Terdaftar] ([Tidak Terdaftar], 2001)
Pengelolaan lingkungan internasional. Dari sudut pandang negara sedang berkembang